A Microbiological Study of Acinetobacter calcoaceticus baumannii with Special Reference to Multidrug Resistance - Longjam, Langamba Angom; Tsering, Dechen Chomu; Das, Dipmala (Journal of Laboratory Physicians, 2021)
Introduction The outbreak of Acinetobacter calcoaceticus baumannii (ACB) is mainly reported to be a notorious pathogens at health-care settings. It is the major problem on the health-care system with high morbidity and mortality rates because of the broad range of antibiotic resistance and lack of understanding the mechanism of developing new antibiotic resistance rapidly. It emphasizes the importance of local surveillance in describing or understanding and predicting microbial resistance patterns so that there will be limited use of antibiotics by developing strategies to control the extensive use of antimicrobial chemotherapy in clinical environment, which is still considered as one of the factors in the emergence of multidrug resistance microorganisms.Objectives The study aims to detect the occurrence rate of ACB infections from various clinical samples, identify the resistance levels to different groups of antimicrobial agents, and the occurrence rate of multidrug resistant (MDR) ACB clinical isolates from a tertiary hospital in Durgapur, West Bengal, India.Material and Methods The study was performed in the Department of Microbiology of the IQ City Medical College and Hospital, Durgapur, West Bengal, India, for the 24 months duration, that is, from January 1, 2018 to December 31, 2019. Altogether 15,800 clinical samples consisting of endotracheal tube aspirates, sputum, pus, blood, catheter tips, urine, tissue, and other body fluids were studied. ACB from clinical samples were identified by its characteristic colonies (nonlactose fermenting, glistening, small mucoid colonies), Gram-staining pattern (Gram-negative coccobacillus), and standard biochemical reactions. It was further confirmed in the Department of Microbiology of the Healthworld Hospital, Durgapur, West Bengal, India, by Vitek2 compact system (bioMerieux, Inc., Durham, North Carolina, United States). Antibiotic susceptibility testing was performed using automated broth microdilutions by Vitek2 compact system (bioMerieux, Inc.) and Kirby-Bauer disk diffusion test on Mueller-Hinton Agar (HiMedia).Results Nonrepetitive 289 ACB were isolated from various clinical samples. A total of 277 (96%) isolates of ACB were MDR strains.Conclusion ACB was mostly isolated from the intensive care unit department and was found to be the most MDR type in the tertiary care hospital by this study.
Keywords: Acinetobacter calcoaceticus baumannii; antibiotic susceptibility testing; MDR strains; Vitek2 compact system